The Factors Influencing The Incident Of Anemia In Pregnant Women In The Working Area Of Sumber Waras Public Health Center I2023 - Kristiani, Kristiani; Eprila, Eprila; Komariah, Nurul (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Abstract Anemia is a condition where red blood cells are insufficient to meet the body's physiological needs. During pregnancy, anemia can be diagnosed if the hemoglobin (Hb) level is less than 11 g/dl. The negative impact of anemia in pregnancy can cause abortion, delayed fetal development, premature birth, LBW, advanced anemia, bleeding and death.Research purposes :Knowing the Factors Associated with the Incident of Anemia in Pregnant Women in the Sumber Waras Community Health Center Work Area in 2023.Research methods: This research is quantitative research with an analytical observational design. This research design uses a cross sectional design. This research was conducted in April-May 2024. The population was 324 pregnant women. The sample for this research was 34 pregnant women who were in the working area of the Sumber Waras Community Health Center, Lubuk Linggau City in 2023.Research result :The results of this study show that the risk factors that influence the incidence of anemia in pregnant women at Sumber Waras Health Center was Fe consumption innon- compliant patients consuming Fe (p=0,006 < 0,05).Conclusion: Of the 32 respondents, there were 16 respondents with high risk Fe consumption compliance and 16 respondents who had a greater risk of experiencing anemia